Characterization of cellular immune system at different ages in water buffalo (Bubalus bubalis) - Maria C. Scata’; Giovanna De Matteis; Francesco Grandoni; Gabriele Di Vuolo; Giovanna Cappelli; Domenico Vecchio (Revista Científica)
The immune system is part of a regulatory network linking physiology, pathophysiology and behavior and it can be regarded as a source of biomarkers for monitoring health and animal welfare. In recent years, there was an increased interest in understanding the immune system of water buffalo due to the growing economic impact of this species. In Italy, buffalo farming constitutes an important livestock resource to produce typical mozzarella cheese. In this study, to characterize the myeloid and lymphoid cells in peripheral blood of buffalo, we assessed three flow cytometric multicolor panels of antibodies: panel 1, with anti CD3, CD4, CD8α and TCR-δ mAbs; panel 2, with anti CD79a and CD21 mAbs; panel 3 with anti CD172a, CD14, CD16, CD335 mAbs. Seventy- eight animals from three farms were divided into 3 groups by age: 80-100 day old calves (N=26); 16-18 months  old heifers (N=26) and 3-6 year old cows in dry status (N=26). Heparinized blood samples were labelled with each antibody cocktail and collected on a CytoFLEX flow cytometer. Significant differences were found by Mann-Whitney test between adult and heifer groups in the mean value of percentage of granulocytes (19.5 vs 13.2; p=0.0158), PBMC (76.3 vs 84.6; p=0.0015), total monocytes (6.8 vs 4.3), T helper (55.6 vs 33.3), T cytotoxic (33.1 vs 54.3), γδ lymphocytes (13.3 vs 32.7) with p<0.0001, and NK cells (5.4 vs 3.5; p=0.0109) and between adult and calf groups in total monocytes (6.8 vs 4.5; p=0.0123), T helper (55.6 vs 27.9), T cytotoxic (33.1 vs 56.1), γδ lymphocytes (13.3 vs 40.4), (p<0.0001), and NK cells (5.4 vs 7.0; p=0.0112). Significant differences between heifer and calf groups were found only in γδ lymphocytes (32.7 vs 40.4), (p=0.0002), and NK cells (3.5 vs 7.0; p<0.0001). Furthermore, the Kruskall-Wallis test highlighted statistical differences in the adult group between the farms in the mean value of percentage of granulocytes (p=0.0030), PBMC (p=0.0120), total (p=0.0152), helper (p=0.0047), cytotoxic (p=0.0019) and γδ T lymphocytes (p=0.0013); total monocytes (p=0.0100), cM and ncM subsets (p=0.0320; p=0.0252); CD21+ B lymphocytes (p=0.0007). The calves showed differences in total monocytes (p=0.0010), cM and ncM subsets (p=0.0335 and p=0.0065), respectively. The heifers showed differences only in the CD21+ B lymphocyte subset (p=0.0439). In summary, this study provides, for the first time, the composition of myeloid and lymphoid cells in this species highlighting large differences between calves, young and adult buffaloes and between different herds. Our results provide a resource for the further study of the immune system and to monitor health and welfare at animal and farm level.